Otolaryngological features in a cohort of patients affected with 22q11.2 deletion syndrome: A monocentric survey. Issue 10 (12th September 2018) - Grasso, Fiorentino; Cirillo, Emilia; Quaremba, Giuseppe; Graziano, Vincenzo; Gallo, Vera; Cruoglio, Letizia; Botta, Carmine; Pignata, Claudio; Motta, Sergio
Abstract : Otorhinolaryngologic manifestations are common in 22q11.2 deletion syndrome (22q11.2DS), but poorly described. This study aimed to better define the ear‐nose‐throat (ENT) phenotype of 22q11.2DS patients, in the attempt to best detect subjects requiring subspecialist intervention. We enrolled 25 patients affected with 22q11.2DS. Anatomic and functional ENT findings were investigated using clinical, laboratory, and instrumental data. Immunophenotype and frequency of infections were evaluated. Univariate and multivariate analyses were performed. ENT anomalies were found in 88% of patients, and in 20% congenital palate defects required surgery. Adenoid or palatine tonsil hypertrophy was noted in 80% and 48%. Forty‐eight percent of subjects had rhinolalia/phonia, severe in half of these. We also found nasal regurgitation or laryngeal penetration/aspiration in 20% and 16%, respectively. Instrumental exams revealed a mild conductive hearing loss in 32% (bilateral in most cases), tympanometric anomalies in 28%, and swallowing abnormalities in 16%. Statistical univariate analysis showed a direct association between rhinolalia/phonia and episodes of laryngeal aspiration ( p = .016) and between tympanometric anomalies and increased adenoid volume ( p = .044). No association between episodes of food aspiration and palatal anomalies was found. Moreover, no statistically significant association was observed between the number of airway infections and the ENT findings. This study contributes to better define the ENT phenotype in patients with 22q11.2DS, helpful to prevent potential complications. Furthermore, the identification of a subcategory of patients may allow the early adoption of specific speech therapy programs to improve the clinical outcome of 22q11.2DS patients.